Rancang Bangun Teknologi Smart Mixing Ice Cream Gelato untuk Pengembangan Bisnis UMKM Kekinian - Widiyanti Widiyanti; Riana Nurmalasari; Marji Marji; Tuwoso Tuwoso; Sh Mohd Firdaus Sh Abdul Nasir (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
Gelato has become a trendy dessert, gaining popularity in the market. However, few UMKM are involved in making contemporary gelato. One reason is the high cost of equipment and the need for special techniques. The success of a gelato product is largely determined by the dough used. Given this situation, UMKM should start using technology to produce gelato dough with higher quality and consistency. The design method for creating gelato dough mixer technology that meets UMKM needs includes problem identification, field studies, design, prototyping, assembly, and analysis. This technology is expected to create an effective, efficient, and high-quality production process. This technology serves not only for stirring but also as a chopper for fruit or other gelato ingredients. This gelato dough mixer technology chops the gelato topping ingredients, which then automatically fall into the gelato mixing chamber and are churned into gelato. The mixing chamber can accommodate a single production process of 30 kg. After mixing is complete, the gelato is removed from the mixing tube through the provided channel, and the results are stored in a container so the packing process can continue.